The modified drive of a metal-cutting machine with the V-belt transmission of increased resource. Issue 1 (January 2021) - Krol, O; Sokolov, V; Tsankov, P
Abstract: The process of the design improving of the V-belt transmission for the metal-cutting machine drive according to the criterion of increased resource is considered. A three-dimensional modeling of the main motion drive structure for multi-operation machine was carried out using the applied library computer aided design KOMPAS-3D. A new approach to the parametric representation of the procedure for constructing a unified profile of a V-belt pulley based on the syntax of the APM WinMachine system is proposed. The idea of constructive change of the standard operating V-belt contour with the corresponding analytical apparatus, which provides increased drawbar power of the transmission, is proposed. Experimental researches on typical sections of V-belts, confirming the increase in the operation reliability of the belt drive have been carried out. provided that the cross-sectional area of the belt remains unchanged